tìm x biết:
a) (2x+1)3=125
Tìm x,biết:
a)2x.(x+4)-(x-1).(2x+3)=0
b)x2-2x-3=0
a) \(2x\left(x+4\right)-\left(x-1\right)\left(2x+3\right)=0\)
\(\Leftrightarrow2x^2+8x-2x^2-x+3=0\)
\(\Leftrightarrow7x=-3\Leftrightarrow x=-\dfrac{3}{7}\)
b) \(x^2-2x-3=0\)
\(\Leftrightarrow\left(x-3\right)\left(x+1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=3\\x=-1\end{matrix}\right.\)
\(a,\Leftrightarrow2x^2+8x-2x^2-x+3=0\\ \Leftrightarrow7x=-3\\ \Leftrightarrow x=-\dfrac{3}{7}\\ b,x^2-2x-3=0\\ \Leftrightarrow\left(x-3\right)\left(x+1\right)=0\\ \Leftrightarrow\left[{}\begin{matrix}x=3\\x=-1\end{matrix}\right.\)
a: Ta có: \(2x\left(x+4\right)-\left(x-1\right)\cdot\left(2x+3\right)=0\)
\(\Leftrightarrow2x^2+8x-2x^2-3x+2x+3=0\)
\(\Leftrightarrow7x=-3\)
hay \(x=-\dfrac{3}{7}\)
b: ta có: \(x^2-2x-3=0\)
\(\Leftrightarrow\left(x-3\right)\left(x+1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=3\\x=-1\end{matrix}\right.\)
Bài 4. Tìm số nguyên x , biết:
a) |x - 2|= 0 b) |x + 3|= 1 c) -3 |4 - x|= -9 d) |2x + 1|= -2
Bài 5. Tìm số nguyên x, biết:
a) (x + 3)mũ 2 = 36 b) (x + 5)mũ 2 =100 c) (2x - 4)mũ 2 = 0 d) (x - 1)mũ 3 = 27
Tìm x, biết:
a) 4x(x + 1) + (3 – 2x)(3 + 2x) = 15
b) 3x(x – 20012) – x + 20012 = 0
`a)4x(x+1)+(3-2x)(3+2x)=15`
`<=>4x^2+4x+9-4x^2=15`
`<=>4x=6`
`<=>x=3/2`
Vậy `S={3/2}`
`b)3x(x-20012)-x+20012=0`
`<=>3x(x-20012)-(x-20012)=0`
`<=>(x-20012)(3x-1)=0`
`<=>` $\left[\begin{matrix} x=20012\\ x=\dfrac{1}{3}\end{matrix}\right.$
Vậy `S={1/3;20012}`
a) 4x(x + 1) + (3 – 2x)(3 + 2x) = 15
⇔4x2 + 4x + (9 – 4x2) = 15
⇔ 4x2 + 4x + 9 – 4x2 = 15
⇔4x = 15 – 9
⇔x=1,5
b)3x(x – 20012) – x + 20012 = 0
⇔3x(x – 20012) – (x – 20012) = 0
⇔(x – 20012)(3x – 1) = 0
⇔x – 20012 = 0 hay 3x – 1 = 0
⇔x = 20012 hoặc x = \(\dfrac{1}{2}\)
Tìm x, biết:
a) \(\dfrac{x-2}{2x+1}=\dfrac{2}{3}\)
b) \(\dfrac{x-2}{2x-1}=\dfrac{-1}{3}\)
a: ĐKXĐ: x<>-1/2
\(\dfrac{x-1}{2x+1}=\dfrac{2}{3}\)
=>\(2\left(2x+1\right)=3\left(x-1\right)\)
=>\(4x+2=3x-3\)
=>\(4x-3x=-3-2\)
=>x=-5(nhận)
b: ĐKXĐ: x<>1/2
\(\dfrac{x-2}{2x-1}=\dfrac{-1}{3}\)
=>\(3\left(x-2\right)=-1\left(2x-1\right)\)
=>\(3x-6=-2x+1\)
=>\(3x+2x=1+6\)
=>5x=7
=>x=7/5(nhận)
Tìm x, biết:
a) x(5 + 3x) – (x + 1)(3x – 2) = 6
b) (2x + ½ )² – (1 – 2x)² = 2
c) x(x + 3) – 2x – 6 = 0
\(a,\Rightarrow5x+3x^2-3x^2-x+2=6\\ \Rightarrow4x=4\Rightarrow x=1\\ b,\Rightarrow\left(2x+\dfrac{1}{2}-1+2x\right)\left(2x+\dfrac{1}{2}+1-2x\right)=2\\ \Rightarrow\dfrac{3}{2}\left(4x-\dfrac{1}{2}\right)=2\\ \Rightarrow6x-\dfrac{3}{4}=2\\ \Rightarrow6x=\dfrac{11}{4}\\ \Rightarrow x=\dfrac{11}{24}\\ c,\Rightarrow\left(x+3\right)\left(x-2\right)=0\\ \Rightarrow\left[{}\begin{matrix}x=2\\x=-3\end{matrix}\right.\)
Tìm x biết:
a)3.(x-2)+2.(x-3)=5
b)(2x-8)2-16=0
c)(2x-1)2-(4x+1).(x-3)=3
a) \(3\left(x-2\right)+2\left(x-3\right)=5\)
\(\Rightarrow3x-6+2x-6=5\)
\(\Rightarrow5x=17\Rightarrow x=\dfrac{17}{5}\)
b) \(\left(2x-8\right)^2-16=0\)
\(\Rightarrow\left(2x-8-4\right)\left(2x-8+4\right)=0\)
\(\Rightarrow\left(2x-12\right)\left(2x-4\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}2x=12\\2x=4\end{matrix}\right.\)\(\Rightarrow\left[{}\begin{matrix}x=6\\x=2\end{matrix}\right.\)
c) \(\left(2x-1\right)^2-\left(4x+1\right)\left(x-3\right)=3\)
\(\Rightarrow4x^2-4x+1-4x^2+12x-x+3=3\)
\(\Rightarrow7x=-1\Rightarrow x=-\dfrac{1}{7}\)
a: Ta có: \(3\left(x-2\right)+2\left(x-3\right)=5\)
\(\Leftrightarrow3x-6+2x-6=5\)
\(\Leftrightarrow5x=17\)
hay \(x=\dfrac{17}{5}\)
b: Ta có: \(\left(2x-8\right)^2-16=0\)
\(\Leftrightarrow\left(2x-4\right)\left(2x-12\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=2\\x=6\end{matrix}\right.\)
a. \(3\left(x-2\right)+2\left(x-3\right)=5\)
\(\Leftrightarrow3x-6+2x-6=5\)
\(\Leftrightarrow5x=17\)
\(\Leftrightarrow x=\dfrac{17}{5}\)
b. \(\left(2x-8\right)^2-16=0\)
\(\Leftrightarrow\left(2x-8-4\right)\left(2x-8+4\right)=0\)
\(\Leftrightarrow4\left(x-6\right)\left(x-2\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x-6=0\\x-2=0\end{matrix}\right.\) \(\Leftrightarrow\left[{}\begin{matrix}x=6\\x=2\end{matrix}\right.\)
c. \(\left(2x-1\right)^2-\left(4x+1\right)\left(x-3\right)=3\)
\(\Leftrightarrow4x^2-4x+1-4x^2+11x+3-3=0\)
\(\Leftrightarrow7x+1=0\)
\(\Leftrightarrow x=-\dfrac{1}{7}\)
Tìm x biết:
a) x(x-3)+2x-6=0
b) (x+1)2-4(x+1)=0
c) (2x+5)(4x+3)-8x(x+3)=10
a: \(x\left(x-3\right)+2x-6=0\)
\(\Leftrightarrow\left(x-3\right)\left(x+2\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=3\\x=-2\end{matrix}\right.\)
b: \(\left(x+1\right)^2-4\left(x+1\right)=0\)
\(\Leftrightarrow\left(x+1\right)\left(x-3\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=-1\\x=3\end{matrix}\right.\)
Câu 3 (1,5 điểm). Tìm x, biết:
a) x + 2006 = 2021
b) 2x – 2016 = 24 x 4
c) 3(2x + 1)3 = 81
a: x=15
c: \(\Leftrightarrow2x+1=3\)
hay x=1
a) \(\Rightarrow x=2021-2006=15\)
b) \(\Rightarrow2x-2016=64\Rightarrow2x=2016+64=2080\Rightarrow x=1040\)
c) \(\Rightarrow\left(2x+1\right)^3=81:3=27\Rightarrow2x+1=3\)
\(\Rightarrow2x=3-1=2\Rightarrow x=1\)
`a) x= 15`
`b) 2x-2016=16\(\times\)4`
`⇔ 2x-2016=64`
`⇔ 2x= 2080`
`⇔ x= 1040`
`c) 3(2x+1)^3 =81`
`⇔ (2x+1)^3 =27`
`⇔ (2x+1)^3 =3^3`
`⇔ 2x+1=3`
`⇔ x= 1`
Tìm x,biết:
a)(2x-3).(x+2)-(4x-2).(x-5)=-16
b)7x2-7=x2-2x+1
a) \(\left(2x-3\right)\left(x+2\right)-\left(4x-2\right)\left(x-5\right)=-16\)
\(\Rightarrow2x^2+x-6-4x^2+22x-10=-16\)
\(\Rightarrow2x^2-23x=0\Rightarrow x\left(2x-23\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}x=0\\x=\dfrac{23}{2}\end{matrix}\right.\)
b) \(7x^2-7=x^2-2x+1\)
\(\Rightarrow7\left(x^2-1\right)-\left(x^2-2x+1\right)=0\)
\(\Rightarrow7\left(x-1\right)\left(x+1\right)-\left(x-1\right)^2=0\)
\(\Rightarrow\left(x-1\right)\left(7x+7-x+1\right)=0\Rightarrow2\left(x-1\right)\left(3x+4\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}x=1\\x=-\dfrac{4}{3}\end{matrix}\right.\)
a) \(\left(2x-3\right)\left(x+2\right)-\left(4x-2\right)\left(x-5\right)=-16\)
\(2x^2+x-6-4x^2+22x-10=-16\)
\(-2x^2+23x-16=-16\)
\(23x-2x^2=0\)
\(x\left(23-2x\right)=0\)
⇔ \(\left[{}\begin{matrix}x=0\\x=\dfrac{23}{2}\end{matrix}\right.\)
b) \(7x^2-7=x^2-2x+1\)
\(7\left(x^2-1\right)=\left(x-1\right)^2\)
\(7\left(x-1\right)\left(x+1\right)-\left(x-1\right)^2=0\)
\(\left(7x+7\right)\left(x-1\right)-\left(x-1\right)^2=0\)
\(\left(x-1\right)\left(7x+7-x+1\right)=0\)
\(\left(x-1\right)\left(6x+8\right)=0\)
⇔ \(\left[{}\begin{matrix}x=1\\x=-\dfrac{4}{3}\end{matrix}\right.\)
tìm x, biết:
a. 3,8 ; (2x)= 1/4: 8/3